Laparoscopic Radical Prostatectomy after Previous Transurethral Resection of the Prostate in Clinical T1a and T1b Prostate Cancer: A Matched-Pair Analysis - Yang, Yi; Luo, Yun; Hou, Guo-Liang; Huang, Qun-Xiong; Lu, Min-Hua; Si-tu, Jie; Gao, Xin (Urology Journal, 2015)
Purpose: To analyze and compare surgical, oncological and functional outcomes of laparoscopic radical prostatectomy (LRP) in patients with and without previous transurethral resection of the prostate (TURP). Materials and Methods: In total, 785 men underwent LRP at our institution from January 2002 to December 2012. TURP had been performed previously in 35 of these patients (TURP group). A matched-pair analysis identified 35 additional men without previous TURP who exhibited equivalent clinicopathological characteristics to serve as a control group. Perioperative complications and surgical, functional, and oncological outcomes were compared between the two groups. Results: The groups were similar in age, body mass index, serum prostate-specific antigen level, and pre- and post-operative Gleason scores. Patients in the TURP group had greater blood loss (231 vs. 139 mL), longer operative times (262 vs. 213 min), a greater probability of transfusion (8.6% vs. 0%), and a higher rate of complications (37.1% vs. 11.4%) compared with the control group. The positive surgical margin rate was higher in the TURP group, but this difference was not statistically significant (P = .179). The continence rates at one year after surgery were similar, but a lower continence rate was identified in the TURP group (42.9% vs. 68.6%) at 3 months. Biochemical recurrence developed in 17.1% and 11.4% of the patients in the TURP and control groups, respectively, after a mean follow-up of 57.6 months. Conclusion: LRP is feasible but challenging after TURP. LRP entails longer operating times, greater blood loss, higher complication rates and worse short-term continence outcomes. However, the radical nature of this cancer surgery is not compromised.